PENANAMAN NILAI-NILAI ISLAM DALAM PERKULIAHAN MATEMATIKA BISNIS PADA PRODI AKUNTANSI SYARIAH IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG - Fahita Faradila; Mahfudz Reza Fahlevi (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
PTKIN was established with a mandate to develop itself as a scientific and cultural institution that provides higher education not only based on the principles of Pancasila but also Islamic principles. Islamic principles and values ​​can actually be instilled in all lines of lectures, both Islamic religious education courses and general knowledge courses, such as business mathematics courses. The purpose of this study is to explain the implementation of inculcating Islamic values ​​in business mathematics lectures at the Islamic Accounting Study Program IAIN SAS Babel in the even semester 2021.2022 academic year. This study uses a descriptive qualitative approach. The research subjects were two Islamic Accounting classes in the second semester. The source of this research is primary data in the form of material presented to students during lectures, while secondary data in this study are such as previous research, books related to business mathematics, and national journals and international journals related to integration, implementation, and value inculcation. - Islamic values ​​in lecture activities in general courses. The results of the research in this paper describe the inculcation of Islamic values ​​in business mathematics lectures on series material (applied to the concept of interest and savings), and linear function material (applied to market equilibrium due to the influence of taxes). Media such as animated video clips to various verses of the Koran and Hadith have been presented and can be used as alternatives in instilling Islamic values ​​in lectures in business mathematics courses.